ANALYSIS OF PREDISPOSITION FACTORS ON PREMATURE RUPTURE MEMBRANES IN POSTPARTUM MOTHERS - Asri Daniyati; Pramita Putri (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Early rupture of membranes is one of the most common pregnancy complications. The incidence of premature rupture of membranes ranges from 5-10% of cases. Preterm premature rupture of membrane occurs in 1% of all pregnancies, 70% of cases of premature rupture of the membranes occur in term pregnancy. In West Nusa Tenggara, 45% of maternal deaths occurred due to bleeding, 14% due to preeclampsia, 1% of prolonged labour (old or stalled openings), 4% infections and 36% of other cases. Aims: The purpose of this study is to analyse some predisposition factors of premature rupture membranes in Maternity Room of General Hospital of West Nusa Tenggara Province in 2012. Methods: This study is observational analytic with cross-sectional design. The population in this study were all maternal mothers at West Nusa Tenggara Provincial Hospital in January - December 2012 with 1027 births and the sample used were 576 samples consisting of 288 case samples and 288 control samples, using systematic random sampling technique. Results: From the result, the age group of 20-35 years old as much as 154 samples (53.5%). The most parity 220 sample (76 .4%), in work mother of 149 samples (51.7%). The result of multivariate analysis using logistic regression showed that age is the most dominant influence which cause the incidence of early rupture of membrane (wald = 20.209) Conclusion: Multivariate analysis showed that there was one variable that proved to have an effect on the incidence of premature rupture of membrane, i.e. mother age with p = 0,000 with OR = 3.441 mean maternal mother with age <20 and> 35 had 3.44 times risk of premature rupture of membranes. Therefore, it is imperative that women are educated in the risk factors and the signs and symptoms of premature rupture of membranes so that in case of membrane breaks, they can seek for immediate treatment.